Lemierre syndrome: Study of 11 cases and literature review. Issue 7 (17th December 2013) - Righini, Christian Adrien; Karkas, Alexandre; Tourniaire, Romain; N'Gouan, Jean‐Michel; Schmerber, Sébastien; Reyt, Emile; Atallah, Ihab
Abstract Background Lemierre syndrome is a rare but serious illness that associates throat infection and thrombosis of the internal jugular vein (IJV) or one of its tributaries with subsequent distant septic emboli. The purpose of our study was to review the pathogenesis, clinical presentation, and treatment of this disease. Methods Patients with confirmed Lemierre syndrome were included in our retrospective monocentric study. All patients had bacteriologic analyses as well as radiologic imaging. Results There were 11 patients in our study (from 1998–2012). Fusobacterium necrophorum was responsible for the infection in 45% of cases. Surgical drainage of pharyngeal, cervical, or mediastinal abscesses was carried out in 8 cases. All patients received broad‐spectrum antibiotics. Six patients were admitted to the intensive care unit (ICU). One patient (9%) died. Conclusion Treatment with broad‐spectrum antibiotics is the primary choice of treatment of Lemierre syndrome. Surgery is indicated in case of abscess formation. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1044–1051, 2014